Identity Passing in Intercultural Performance of K-pop Cover Dance. Issue 5 (2nd September 2020) - Oh, Chuyun
ABSTRACT: The global phenomenon of K-pop cover dance indicates the rise of imitation in social media and its production value wherein identity passing is necessary. Employing performance ethnography, this article analyzes two female K-pop cover dancers in San Diego, CA and examines their embodied labour and (dis)privilege in their intercultural performance of K-pop. Their stories disclose discrepancy than solidarity within the racial and ethnic minority fandom and (in)ability of identity passing based on sociocultural and economic resources at the intersection of age, race, ethnicity, class, education, and family. Yet, a daunting reality further inspires fans' dreams to be like K-pop idols.